1972
DOI: 10.1001/archinte.1972.03650020023005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Patients With the "Partial" Deficiency of the X-Linked Uricaciduria Enzyme

Abstract: Patients with gout associated with "partial" deficiency of hypoxanthine-guanine phosphoribosyltransferase have clinically distinctive findings. Since the disorder is inherited as an X-linked recessive trait, all 21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The levels of HPRT activity in Lesch-Nyhan individuals vary from zero to a few per cent of normal. Although some studies have reported a correlation between the extent of the en7yme deficiency and the severity of neurologic dysfunction (GREENE, 1972: SEEGMILLER. 1976).…”
mentioning
confidence: 99%
“…The levels of HPRT activity in Lesch-Nyhan individuals vary from zero to a few per cent of normal. Although some studies have reported a correlation between the extent of the en7yme deficiency and the severity of neurologic dysfunction (GREENE, 1972: SEEGMILLER. 1976).…”
mentioning
confidence: 99%